From competition to cooperation: the global palm oil "sustainability turn" as a turning point for the Malaysia-Indonesia "special relationship" - Varkkey, Helena (Nanyang Technological University, 2023)
Palm oil is the source of a common identity between Malaysia and Indonesia, the two largest palm oil producers globally. As with many other socio-cultural aspects of the Malaysia-Indonesia “special relationship”, palm oil has also led to heightened competition between both nations. However, recent negative sentiments towards palm oil originating from sustainability-conscious markets in the north have threatened both states’ access to important export markets. This paper examines how these developments have marked an important turning point in Malaysia-Indonesia relations. Faced with such external pressures, both states are now increasingly reliant on each other’s continued prominence for their own market survival — their shared strategic interests tending to facilitate cooperation instead of conflict or competition. This paper takes the Malaysian perspective in illustrating the shift from competition to cooperation within the palm oil sector. Of particular interest are the issues over transboundary haze, where Malaysia’s responses have been increasingly geared towards appeasement, restrained by concerns about related fallouts in the palm oil sector.